Potential Management of the Enterprise from the Position of Functional Approach - KNIAZ SVIATOSLAV; HEORHIADI NELLІ; SAI LESIA; SHCHEBEL ANDRII; MOROZ SVITLANA; KALASHNYK OLENA; SPITSYNA ANHELINA; KYRYCHENKO OLENA; VILHUTSKA ROKSOLANA; PEREDALO KHRYSTYNA; MYSKIV IRYNA; SHAYNER HANNA (Communications of International Proceedings, 2020)
The potential of the enterprise is considered as a system of opportunities to achieve development goals within the functions defined by the structure of the enterprise. In turn, the management of the enterprise potential is disclosed as a specific function of management. It is proved that it is based on a specific object of management - of the enterprise potential. It is substantiated that the management of this object is carried out by the heads of the enterprise using management methods and technologies, the selection and application of which is carried out within the general management functions (planning, organizing, motivating, controlling and regulating). Since the potential of the enterprise is a complex object of management, which includes production, marketing, investment and other potentials, there is a reason to believe that the goals of managing the potential of the enterprise is a complex, hierarchical system. Their implementation requires constant monitoring and regulation of the object of management.
Keywords: Enterprise; Potential; Management System; Functional Approach; Management Goals.